Advances in Traditional Chinese Medicine for chronic obstructive pulmonary disease through multi-omics approaches - Yang, Kun; Wang, Jun; Ma, Yizhao; Zhang, Hailong (Frontiers in Cell and Developmental Biology, 2026)
Chronic obstructive pulmonary disease (COPD) is a common and complex heterogeneous chronic inflammatory airway disorder characterized by multifactorial pathogenesis and limited therapeutic options. It remains one of the leading causes of morbidity and mortality worldwide, severely impairing patients’ quality of life and life expectancy. Traditional Chinese Medicine (TCM), with its holistic perspective, syndrome differentiation, and multi-component formulations, is widely used in the adjunctive treatment and rehabilitation of COPD. Evidence suggests that TCM can relieve symptoms, reduce acute exacerbations, and enhance quality of life. However, the “multi-component-multi-target-multi-pathway” nature of TCM formulas has long made their mechanisms difficult to systematically elucidate. In recent years, the rapid development of high-throughput multi-omics technologies has provided unprecedented opportunities to decipher the systems biology mechanisms underlying TCM treatment of COPD. Multi-dimensional data from network pharmacology, genomics, transcriptomics, proteomics, metabolomics, and microbiomics can comprehensively reveal disease-related molecular changes. These findings provide scientific evidence for the objectification of TCM syndromes, the identification of biomarkers, and the clarification of multi-target mechanisms in key herbal formulas, such as Bufei Jianpi granules. Moreover, multi-omics studies have also promoted exploration of emerging fields such as the “lung-gut axis”, providing new theoretical perspectives for understanding the complex pathological processes of COPD. This review systematically summarizes recent advances in TCM-based prevention and treatment of COPD using multi-omics strategies. Key progress includes the application of network pharmacology and pharmacogenomics in component-target prediction, the role of transcriptomics/proteomics in molecular target validation, and the value of metabolomics and microbiomics in uncovering metabolic reprogramming and lung-gut axis regulation. Integrated multi-omics approaches also demonstrate significant potential in biomarker discovery and the development of precision TCM. In addition, this review provides a critical evaluation of current trends, potential breakthroughs, challenges, and opportunities in advancing TCM from empirical medicine toward evidence-based and precision medicine, aiming to offer systematic and comprehensive theoretical foundations and research perspectives for TCM-based COPD therapy.